THE EFFECT OF OPEN ENDED LEARNING (OEL) MODEL TOWARDS STUDENTS’ READING COMPREHENSION SKILL AT SMAN 1 KERUAK - Diansyah Naqsabandi; Muliani Muliani (Lembaga Penelitian dan Pendidikan Mandala, 2020)
This research is aimed at finding out the effect of Open Ended Learning (OEL) Model toward Students’ Reading Comprehension Skill at SMAN 1 Keruak. The research is Quantitative Experimental Research. The design is used quasi experimental with non-equivalent. The population of the study was the first grade students of SMAN 1 Keruak consists of nine classes. Two classes were chosen as the sample, those were IPS I as the experimental group consisting of 25 students and IPS IV as the control group consisting of 25 students. They were chosen by using cluster sampling technique. Experimental group was treated by Open Ended Learning (OEL) Model and control group was treated by Direct Instruction (DI) Model. The instrument that used was reading test in form of multiple choices consisting of 30 items. Then the score were analyzed by using SPSS_26. It shows that the mean score of experimental group is 52.64 the maximum score is 76, the minimum score is 33, and the standard deviation is11.636. While the maximum score of control group is 70, the minimum score is 37, the mean score is 49.08, and the standard deviation is 11.683. The value of sig. (2-tailed) is 0.006 where the value of sig. (2-tailed) is lower than the significance level (0.05). Therefore based on the result of the statistical analysis, it can be concluded that there is positive effect of Open Ended Learning (OEL) Model towards students’ reading comprehension skill at the first grade students of SMAN 1 Keruak. In other words, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected.